2007
DOI: 10.1016/j.mce.2007.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor signaling is an unstable feature of the gonadotropic LβT2 cell line

Abstract: The murine, gonadotropic LbetaT2 cell line was assessed as a potential in vitro model to analyze estrogen receptor (ER)-mediated regulation of luteinizing hormone (LH) synthesis and secretion. In agreement with limited literature data, repeated exposure to (sub) physiological concentrations of gonadotropin-releasing hormone enhanced LHbeta-subunit gene expression, being the rate-limiting step of LH synthesis, and the corresponding LH secretory response. However, in the same subclone of the LbetaT2 cell line, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Also, we were unable to replicate the results in Zhang et al (2006) with ERE-tk-luc (data not shown). Recently, it was reported that some batches of LbT2 cells are unresponsive to estrogens (Eertmans et al 2007) and this seems to be the case with ours. Therefore, an assessment of the effects of activinregulated Hsd17b1 expression on gonadotropin synthesis must await an estrogen-sensitive batch of LbT2 cells or a different cell system.…”
Section: Discussionsupporting
confidence: 82%
“…Also, we were unable to replicate the results in Zhang et al (2006) with ERE-tk-luc (data not shown). Recently, it was reported that some batches of LbT2 cells are unresponsive to estrogens (Eertmans et al 2007) and this seems to be the case with ours. Therefore, an assessment of the effects of activinregulated Hsd17b1 expression on gonadotropin synthesis must await an estrogen-sensitive batch of LbT2 cells or a different cell system.…”
Section: Discussionsupporting
confidence: 82%
“…Although the LbT2 cell line has been found to express AR, ERa, and PR proteins, the functional activity of these receptors has been questioned with investigators commonly overexpressing the relevant receptor when analyzing transcriptional regulation in these cells. 60,73,74 Nevertheless, although the estrogen response has been reported to be unstable in this cell line, we observed small but statistically significant changes in mRNA expression of a number of transcription factors following estradiol treatment (Figure 8). 73 Furthermore, responses were not substantially different in cells transfected with the AR or PR expressing plasmids prior to hormonal treatment (data not shown), arguing against a lack of functional or adequate receptor number in this cell line as a cause for discrepancies between the primary and immortalized cells.…”
Section: Discussionmentioning
confidence: 67%
“…Because androgen stimulation in the presence of the endogenous L␤T2 AR is relatively weak, several of these studies have amplified the steroid hormone response by cotransfecting AR expression constructs, a method we have adopted in the current study. The same strategy has been employed to study ER, PR, and GR in L␤T2 cells (35,36,52,68,69). In the studies reported here, the rPACAP promoter was robustly activated by androgen in the context of the immortalized L␤T2 gonadotrope, with activation that is dependent on the presence of AR.…”
Section: Discussionmentioning
confidence: 98%
“…Although early studies reported AR immunoreactivity comparable to that of mouse and rat pituitary extracts, more recent studies have reported difficulty detecting endogenous AR, concluding that the overall level of endogenous AR in L␤T2 cells is low (35,36,46). Similarly, unstable expression of ER, progesterone receptor (PR), and glucocorticoid receptor (GR) has been reported in L␤T2 cells despite having readily measurable levels of mRNA (35,52). In light of this, we wished to confirm that L␤T2 cells, in our hands, retained the ability to express AR and respond to androgen stimulation in order to support use of this cell line as a model system to study androgen regulation of PACAP expression.…”
Section: Expression Of Ar Mrna and Protein In Gonadotropesmentioning
confidence: 99%